The PPARy agonist, ros,glitazone, attenuates airway inflammation and remodeling via heme oxygenase-1 in murine model of asthma - Jing XU Yan-ting ZHU Gui-zuo WANG Dong HAN Yuan-yuan WU De-xin ZHANG Yun LIU Yong-hong ZHANG Xin-ming XIE Shao-jun LI Jia-mei LU Lu LIU Wei FENG Xiu-zhen SUN Man-xiang LI (中国药理学报：英文版, 2015)
Aim： Rosiglitazone is one of the specific PPARy agonists showing potential therapeutic effects in asthma. Though PPARy activation was considered protective in inhibiting airway inflammation and remodeling in asthma, the specific mechanisms are still unclear. This study was aimed to investigate whether heme oxygenase-1 （HO-1） related pathways were involved in rosiglitazone-activated PPARy signaling in asthma treatment. Methods： Asthma was induced in mice by multiple exposures to ovalbumin （OVA） in 8 weeks. Prior to every OVA challenge, the mice received rosiglitazone （5 mg/kg, po）. After the mice were sacrificed, the bronchoalveolar lavage fluid （BALF）, blood samples and lungs were collected for analyses. The activities of HO-1, MMP-2 and MMP-9 in airway tissue were assessed, and the expression of PPARy, HO-1 and p21 proteins was also examined. Results： Rosiglitazone administration significantly attenuated airway inflammation and remodeling in mice with OVA-induced asthma, which were evidenced by decreased counts of total cells, eosinophils and neutrophils, and decreased levels of IL-5 and IL-13 in BALF, and by decreased airway smooth muscle layer thickness and reduced airway collagen deposition. Furthermore, rosiglitazone administration significantly increased PPARy, HO-1 and p21 expression and HO-1 activity, decreased MMP-2 and MMP-9 activities in airway tissue. All the therapeutic effects of rosiglitazone were significantly impaired by co-administration of the HO-1 inhibitor ZnPP. Conclusion： Rosiglitazone effectively attenuates airway inflammation and remodeling in OVA- induced asthma of mice by activating PPARY/HO-1 signaling pathway.